MENINGKATKAN KARAKTER SISWA DI ERA TEKNOLOGI MELALUI NOVEL CEROS DAN BATOZAR - Anisa Puspita Sari; Wilsa Fentani; Rifky Sandi Kurniawan; Dewi Kusumaningsih (Jurnal Bastra (Bahasa dan Sastra), 2025)
This article discusses efforts to improve student character in the technological era through the novels “Ceros and Batozar” as learning media. In an educational context that is increasingly influenced by technological advances, it is important to apply character values ​​in learning activities. The novel was chosen as an effective means of exploring relevant character values, such as honesty, intelligence, toughness, and caring. These values ​​are very important for students' personal development in facing the challenges of the times. Through the implementation of learning methods such as group discussions, problem-based learning (PBL), and project-based learning (PjBL), students are invited to analyze and discuss these values ​​and relate them to the social problems around them. In this way, it is hoped that students will not only improve their communication skills and creativity, but also strengthen the internalization of character values ​​that are important in life. The main aim of this article is to identify the role of the “Ceros and Batozar” novels in improving students' personality characteristics by highlighting the values ​​contained in the narrative, as well as how these values ​​can be internalized by readers. The research was conducted using a qualitative approach with data analysis techniques. Data were analyzed using thematic techniques which allowed researchers to identify, analyze and discuss themes related to the values ​​of the characters in the novel. It is hoped that this article can provide understanding to educators in developing effective learning strategies to strengthen students personalities in the digital era, as well as strengthening value and character-based learning that is relevant to current technological developments.